“Talleres de capacitación para desarrollar las competencias comunicativas en el trabajo áulico” - Maza Jaramillo, Gisela Alejandra (2024)
This research project focuses on the existence of a communication deficit between teachers and students at the initial level, due to the fact that they do not have academic training related to the area of communicative competencies. The objective of the research was to elaborate workshops for the development of communicative competencies in the classroom work of teachers, through the application of the expository method for early education students of the "Coronel Germánico Ribadeneira Valencia" Educational Unit of the San Juan de Pastocalle parish. The approach of the work is of a qualitative and constructivist type where a deep analysis was carried out since it focuses on understanding the experiences and behaviors of the beneficiaries. The type of research is exploratory in nature, and instruments such as interview guides and observation cards were used with teachers in similar conditions, which resulted in empty learning in children due to the lack of good communication on the part of teachers. Based on the data collected, 6 workshops were designed taking into account: phases, objectives, strategies, methods, time and resources for the development of the workshops. This study led to the conclusion that: from the data collected, the communicative competencies facilitate the teacher's acquisition of clear and effective communication, including oral and written expression and listening in a more active way with the use of workshops, which is necessary to improve teacher-student communication.